Minimal Self and Timing Disorders in Schizophrenia: A Case Report - Martin, Brice; Franck, Nicolas; Cermolacce, Michel; Coull, Jennifer T.; Giersch, Anne (Frontiers in Human Neuroscience, 2018)
For years, phenomenological psychiatry has proposed that distortions of the temporal structure of consciousness contribute to the abnormal experiences described before schizophrenia emerges, and may relate to basic disturbances in consciousness of the self. However, considering that temporality refers mainly to an implicit aspect of our relationship with the world, disturbances in the temporal structure of consciousness remain difficult to access. Nonetheless, previous studies have shown a correlation between self disorders and the automatic ability to expect an event in time, suggesting timing is a key issue for the psychopathology of schizophrenia. Timing disorders may represent a target for cognitive remediation, but this requires that disorders can be demonstrated at an individual level. Since cognitive impairments in patients with schizophrenia are discrete, and there is no standardized timing exploration, we focused on timing impairments suggested to be related to self disorders. We present the case report of AF, a 22 year old man suffering from schizophrenia, with no antipsychotic intake. Although AF shows few positive and negative symptoms and has a normal neurocognitive assessment, he shows a high level of disturbance of Minimal Self Disorders (SDs) (assessed with the EASE scale). Moreover, AF has a rare ability to describe his self and time difficulties. An objective assessment of timing ability (variable foreperiod task) confirmed that AF had temporal impairments similar to those previously described in patients, i.e. a preserved ability to distinguish time intervals, but a difficulty to benefit from the passage of time to expect a visual stimulus. He presents additional difficulties in benefitting from temporal cues and adapting to changes in time delays. The impairments were ample enough to yield significant effects with analyses at the individual level. Although causal relationships between subjective and objective impairments cannot be established, the results show that exploring timing deficits at the individual level is possible in patients with schizophrenia. Besides, the results are consistent with hypotheses relating minimal self disorders (SDs) to timing difficulties. They suggest that both subjective and objective timing investigations should be developed further so that their use at an individual level can be generalized in clinical practice.